Mapping Visualization of Maritime Technology Study in Indonesia with Blibiometric Analysis Using VoSviewer - Rizqiya Windy Saputra; M. Sapril Siregar (Jurnal Pendidikan Multimedia (Edsence), 2022)
Indonesia is a large country with many spreading archipelagos. The condition makes Indonesia a potential country in maritime sectors. The potential condition establish maritime technology is a topic that has begun to interest many researches. The strong desire of researcher will also get support from the many sources of citations that are now appearing and can be used as references. Even though it has a wide area of expertise, the researches concerning maritime technology is very little at present. This research aims to collect the trends of maritime technology research in Indonesia by performing bibliometric analysis from scientific papers indexed by partly free scholarly database named Dimension. This research analyzes the numbers of document published, the most cited papers, and the productivity of maritime researchers in specific area of maritime technology. Some keywords focused on this researched were minned by clustering using VOSviewer. As the result, this study hopefully provide an overview of current research on maritime technology in Indonesia and provide the right direction for researchers with maritime technology research interest.